The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/bjet.12611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the use of interactive E‐books by intensive care unit patients' family members: Anxiety, learning performances and perceptions

Abstract: In an intensive care unit (ICU), patients' families play a very important role; however, they often lack medical knowledge and are extremely anxious, which could affect their ability to take care of the patients. The effects of giving conventional paper‐based instruction are limited in terms of improving patients' families' understanding of the facilities and the rules in the ICU and in reducing their anxiety. Therefore, in this study, an interactive e‐book was developed to present the nursing education conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…As Maganty et al (2018) informed that compared with conventional printed materials, interactive learning exhibited great potential in promoting patients' learning motivation and effects. It has now been demonstrated that interactive design tends to facilitate patients learning outcomes by presenting related knowledge in an interactive manner (Lee, Wang, et al, 2019). Research has tended to focus on the combination of interactive functions and learning content to provide tasks, guidance, and feedback to learners (Sung et al, 2019; Suppan et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…As Maganty et al (2018) informed that compared with conventional printed materials, interactive learning exhibited great potential in promoting patients' learning motivation and effects. It has now been demonstrated that interactive design tends to facilitate patients learning outcomes by presenting related knowledge in an interactive manner (Lee, Wang, et al, 2019). Research has tended to focus on the combination of interactive functions and learning content to provide tasks, guidance, and feedback to learners (Sung et al, 2019; Suppan et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The major advantages of mobile devices include shareability, creativity and multimedia features (Shadiev et al, 2018). The mobile contextual interactive environment facilitates the delivery of healthcare education by nursing staff, as the interactive environment not only frequently updates the healthcare information but also provides interactions with audio‐visual information and social networking applications (Lee, Wang, et al, 2019; Lin et al, 2020). Likewise, these advantages show the huge potential to facilitate remote information sharing and education for caregivers and minimize their risk of infection (Taylor et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations